Enhancement thermal stability of polyetherimide-based nanocomposites for applications in energy storage. (5th January 2021) - Miao, Weijun; Chen, Hanxi; Pan, Zhongbin; Pei, Xueliang; Li, Long; Li, Peng; Liu, Jinjun; Zhai, Jiwei; Pan, Hui
Abstract: Improving thermal stability of high-performance polymer-based nanocomposite films for electrical energy storage is essential to meet ever-increasing demands for the electrical industry, especially at harsh environment applications. Here, the polyetherimide (PEI)-based composites films are prepared via grafting method in the presence of SrTiO3 (ST) nanofillers to substantially improved capacitive performances at elevated temperature. The composites films with the optimized filler compositions show a high discharged energy density of 6.76 J/cm 3 under 600 MV/m at room temperature. Meantime, excellent high-temperature discharged energy density of 6.6 J/cm 3 at 100 °C for the composites films is also achieved, which is superior to most of the previously reported. The simulations further demonstrate that the ST nanoparticles embedded into the composites films could effectively improve heat dissipation in comparison with pristine PEI matrix, resulting in enhancement high-temperature energy storage capabilities. This work gives considerable promise for high energy density polymer-based nanocomposite films capacitors under harsh environments. Graphical abstract: Image 1 Highlights: SrTiO3 nanoparticles/polyetherimide nanocomposite film are designed and prepared by grafting method. The composite film obtains excellent high-temperature energy storage performance. An excellent high-temperature discharged energy density of 6.6 J/cm 3 at 100 °C is achieved.